Aspectos histológicos, bioquímicos e imunológicos da infecção experimental por Leishmania (Leishmania) major no modelo de implante de parafina em camundongos - Vanessa Martins Ferreira (2008)
The paraffin-tablets implantation associated to an experimental L. major infection, in the subcutaneous tissue of C57BL/6 mice, is able to produce a chronic inflammatory reaction associate to an increment of the parasitism. The aim of this work was to investigate possible modifications in the immune response (Th1 towards to Th2 response) in C57BL/6 mice. BALB/c and C57BL/6 mice were divided in three groups(n=5 in each group). The first one (L+P) received the paraffin-tablets implantation associated to an experimental infection with L. major; the second group (P) received only the implantation and the group 3 (L) received only the parasites. Fragments of dorsal skin tissue and inflammatory capsule were obtained after 07, 21 and 30 days post-infection. In the L+P group, 07 days post-infection, the skin fragments showed a diffuse chronic inflammatory reaction with granulomatous tissue formation (inflammatory capsule). After 21 days, the chronic inflammatory response and the parasite tissue load were higher than 07 days. The groups L and P showed the same histological picture, but the intensity was lower intense than observed in the groupL+P. The N-acetil--D-glucosaminidase (NAG) enzyme activity was higher in 21 days in the inflammatory capsule obtained from C57BL/6 mice, but it was not directly related to a lower parasite load. In despite of IFN-gamma production, a higher IL-10 expression was detected at the same time of the parasite load pick (21 days) in both skin and inflammatory capsule of C57BL/6 animals (L+P group). Thus, regulatory T lymphocytes might be a candidate for IL-10 production, because higher levels of the CXCL9 chemokine expression were detected in inflammatory capsule of these animals. The expression levels of CCL3 (MIP-1a) was higher than CCL2 (MCP-1) ant it is could be indicating a strict correlation to the parasite load pick observed at 21 days. We have concluded that C57BL/6 Th1 immune response did not toward to theTh2 response, besides C57BL/6 animals presented the same histological picture of the BALB/c animals.